The social and behavioural aspects of climate change: linking vulnerability, adaptation and mitigation (Sheffield, 2010)
"Over the past few years, and certainly since the publication of the Stern Report, there has been increasing recognition that climate change is not only an environmental crisis, but one with important social and economic dimensions. There is now a growing need for multi-disciplinary research and for the science of climate change to be usefully translated for policy-makers."